EFFECT OF FERMENTED CHUB MACKEREL EXTRACT ON LIPID METABOLISM OF DIABETIC RATS - Santoso, U.; Ishikawa, S.; Tanaka, K. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The present study was conducted to evaluate the effect of fermented chub mackerel extract(FCME) on lipid metabolism in diabetic rats. Four week-old male Wistar rats were divided into threegroups based on weight. All rats were induced with diabetes mellitus by single intraperitoneal injectionof streptozotocin at 45 mg/kg body weight. Thereafter, they were randomly distributed to threetreatments with 7 rats assigned to each treatment. One group was the control with no additive, and twotreatmentgroups were given the purified diets supplemented with 1% or 2% FCME. Experimentalresults showed that in comparison to the control, diabetic rats fed FCME increased feed intake (P<0.01)and body weight gain (P<0.05). FCME inclusion significantly reduced the activities of acetyl-CoAcarboxylase (P<0.01) and fatty acid synthetase (P<0.05) in diabetic rats. FCME significantly increasedcholesterol 7 -hydroxylase with no effect on HMG-CoA reductase activity. FCME had no effect onhepatic triglyceride, free cholesterol and phospholipid. FCME inclusion at 1% level significantlyreduced serum triglyceride. FCME significantly increased HDL-cholesterol (P<0.05) with no effect onLDL + VLDL-cholesterol, and significantly reduced atherogenic index. FCME did not significantlyaffect serum insulin and glucose concentration. In conclusion, FCME supplementation altered lipidmetabolism in diabetic rats. FCME supplementation reduced the risk of atherosclerosis in diabetic rats.